Spirituality, Atrocities and IT – German Images of India (Politeja, 2016)
Imaginations of India have been an important ingredient of the German literary and media landscape since the end of the 18th century. Though they are highly diverse, these images are equally often emotionally charged and situated somewhere between euphoric glorifications and deprecating condemnations. When Germany and India were celebrating the 60th anniversary of their diplomatic relations, the time had come to investigate why Germans until today, even in the so‑called age of information, have so diverse perceptions of India. By reference to the three dominant German images of India, this article seeks to understand the various factors that influence our perception of another culture.